2004
DOI: 10.1016/s0212-6567(04)78924-6
|View full text |Cite
|
Sign up to set email alerts
|

Enseñanza de la reanimación cardiopulmonar básica en población general

Abstract: The basic HLR courses for the general public provide useful theoretical and practical training and manage to improve peoples ability to react correctly and so resolve emergency situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The immediate action in an out-of-hospital cardiac arrest (OHCA) is essential to increase survival rates, which includes an immediate and effective application of basic life support (BLS) measures and the use of Automatic External Defibrillators (AEDs) by the trained laypersons, who are generally relatives, friends, teachers or passers-by. 1 With this objective in mind, according to International Liaison Committee on Resuscitation (ILCOR), the European Resuscitation Council (ERC), among others, the recommends the teaching, training and retraining of laypeople, although both the duration and the characteristics of the training programs have yet to be ascertained 2 and in addition, proposes the online teaching of theoretical knowledge, while prioritizing hands-on training in the face-to-face part. 3 , 4 , 5 However, previous studies have shown the different existing educational programs on BLS, and they differ in terms of the applied methodology, duration and contextualization.…”
Section: Introductionmentioning
confidence: 99%
“…The immediate action in an out-of-hospital cardiac arrest (OHCA) is essential to increase survival rates, which includes an immediate and effective application of basic life support (BLS) measures and the use of Automatic External Defibrillators (AEDs) by the trained laypersons, who are generally relatives, friends, teachers or passers-by. 1 With this objective in mind, according to International Liaison Committee on Resuscitation (ILCOR), the European Resuscitation Council (ERC), among others, the recommends the teaching, training and retraining of laypeople, although both the duration and the characteristics of the training programs have yet to be ascertained 2 and in addition, proposes the online teaching of theoretical knowledge, while prioritizing hands-on training in the face-to-face part. 3 , 4 , 5 However, previous studies have shown the different existing educational programs on BLS, and they differ in terms of the applied methodology, duration and contextualization.…”
Section: Introductionmentioning
confidence: 99%